Precision enzyme discovery through targeted mining of metagenomic data - Ariaeenejad, Shohreh; Gharechahi, Javad; Foroozandeh Shahraki, Mehdi; Fallah Atanaki, Fereshteh; Han Jianlin; Ding, Xue-Zhi; Hildebrand, Falk; Bahram, Mohammad; Kavousi, Kaveh; Hosseini Salekdeh, Ghasem (Springer, 2024)
Metagenomics has opened new avenues for exploring the genetic potential of uncultured microorganisms, which may serve as promising sources of enzymes and natural products for industrial applications. Identifying enzymes with improved catalytic properties from the vast amount of available metagenomic data poses a significant challenge that demands the development of novel computational and functional screening tools. The catalytic properties of all enzymes are primarily dictated by their structures, which are predominantly determined by their amino acid sequences. However, this aspect has not been fully considered in the enzyme bioprospecting processes. With the accumulating number of available enzyme sequences and the increasing demand for discovering novel biocatalysts, structural and functional modeling can be employed to identify potential enzymes with novel catalytic properties. Recent efforts to discover new polysaccharide-degrading enzymes from rumen metagenome data using homology-based searches and machine learning-based models have shown significant promise. Here, we will explore various computational approaches that can be employed to screen and shortlist metagenome-derived enzymes as potential biocatalyst candidates, in conjunction with the wet lab analytical methods traditionally used for enzyme characterization.